Informing the public about a pandemic - Francis de Véricourt; Huseyin Gurkan; Shouqiang Wang (European School of Management and Technology (ESMT), 2020)
This paper explores how governments may efficiently inform the public about an epidemic to induce compliance with their confinement measures. Using an information design framework, we find that governments have an incentive to either downplay or exaggerate the severity of the epidemic if the government heavily prioritizes the economy over population health or vice versa. Importantly, we find that the level of economic inequality in the population has an effect on these distortions. The more unequal the disease's economic impact on the population is, the less the government exaggerates and the more it downplays the severity of the epidemic. When the government weighs the economy and population health sufficiently equally, however, the government should always be fully transparent about the severity of the epidemic.
More recent version: http://hdl.handle.net/10419/229934
Keywords: 650; Public Health; Epidemic Control; Information Design; Strategic Behavior